2000
DOI: 10.1136/bmj.320.7247.1429
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and remission rates of lower urinary tract symptoms at one year in women aged 40-60: longitudinal study

Abstract: Objectives To determine the incidence and rates of remission of lower urinary tract symptoms at one year in women aged 40-60, and to assess factors associated with remission. Design Ongoing longitudinal cohort study. Setting One rural and one urban county in Denmark. Participants 4000 women recruited on a random basis, 2860 of whom were followed up at one year. Measurements Incidence and rates of remission of lower urinary tract symptoms. Results Prevalence, incidence, and rates of remission of lower urinary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
66
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 20 publications
(33 reference statements)
13
66
1
1
Order By: Relevance
“…Two population-based studies 11,12 of women younger than age 60 years reported mean annual incidences ranging from 4% to 5%. Also, similar to our observation of a 1.8% average 1-year incidence of leaking at least once per week, Moller et al 13 Several limitations of this study should be considered. Classification of incontinence frequency and type was based on self-report.…”
Section: Commentsupporting
confidence: 56%
“…Two population-based studies 11,12 of women younger than age 60 years reported mean annual incidences ranging from 4% to 5%. Also, similar to our observation of a 1.8% average 1-year incidence of leaking at least once per week, Moller et al 13 Several limitations of this study should be considered. Classification of incontinence frequency and type was based on self-report.…”
Section: Commentsupporting
confidence: 56%
“…Seven studies examined the incidence of UI in Europe [20,21,22,23,24,25,26]. One study used a validated questionnaire (BLUTS) to investigate UI [22].…”
Section: Resultsmentioning
confidence: 99%
“…16 Annual rates of UI incidence vary from 1% to 11% and of UI remission from 5% to 11%. [17][18][19][20][21][22][23][24] Most studies assessing the causes of UI are cross-sectional and therefore cannot assess UI as a dynamic condition. Moreover, the few longitudinal studies have had relatively limited follow-ups (2-5 years) or no interval evaluation of the UI evolution during the study period.…”
Section: Introductionmentioning
confidence: 99%